Changing political culture and electoral behavior in Malaysia - Moten, Abdul Rashid (Taylor & Francis Group, LLC, 2011)
The reform movement of 1998 and the general elections in 1999 are argued by many to have brought about a shift in Malaysian political culture, which became evident in 2008 elections. Studies conducted before 1999, based on fragmentary evidence, pictured Malaysia as having a “subject” political culture. The post-2008 survey data presents a picture of a high level of participation approximating the “participant” political culture. This change in political culture is due, among other reasons, to the poor regime performance, the emergence of civil society and the availability of alternative media. The 2008 elections, which witnessed the emergence of a “strong” opposition in the parliament, reflect the maturity of theMalaysian electorate, noticeably since 2004, which augurs well for democracy in the country.